2015
DOI: 10.3389/fpsyg.2015.00655
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected online gambling disorder in late-life: a case report

Abstract: Background: The lifetime prevalence of problem or Gambling disorder (GD) in the elderly (i.e., those over 60 years old) is reported to range from 0.01 to 10.9%. Research has identified several specific risk factors and vulnerabilities in the elderly. Since the late 1990s, an increase in online GD has been observed in the youth population, whereas casinos, slot machines, and bingo seem to be the activities of choice among the elderly. Interestingly, online GD has not been described in the elderly to date.Case D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 73 publications
1
11
0
Order By: Relevance
“…(2014) explored age as a moderator of gambling pathology and observed that the older the patient, the higher the comorbid health problems and the emotional distress they presented (measured by means of the SCL-90-R). Bearing these findings in mind, gambling behaviors in older adults could be associated with a need to ameliorate negative feelings and to cope with stressful situations related to older age (Sauvaget et al., 2015; Subramaniam et al., 2015).…”
Section: Discussionmentioning
confidence: 98%
“…(2014) explored age as a moderator of gambling pathology and observed that the older the patient, the higher the comorbid health problems and the emotional distress they presented (measured by means of the SCL-90-R). Bearing these findings in mind, gambling behaviors in older adults could be associated with a need to ameliorate negative feelings and to cope with stressful situations related to older age (Sauvaget et al., 2015; Subramaniam et al., 2015).…”
Section: Discussionmentioning
confidence: 98%
“…The literature on older individuals’ online gambling as well as on gender differences in online gambling is scarce [ 60 ]. In general, we know that females tend to favour non-skill games such as slot machines and bingo [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that older adults favor casinos, slot machines and bingo as gambling activities (Tse, Hong, Wang, & Cunningham-Williams, 2012), with distinct motivations to gamble (entertainment and leisure more than money and rewards) (Martin, Lichtenberg, & Templin, 2011). Overall, online problem gambling studies conducted among older adults remain scarce (Sauvaget et al, 2015).…”
Section: Demographicsmentioning
confidence: 99%